2011
DOI: 10.5504/bbeq.2011.0003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Crude Lipase fromRhizopus Arrhizusand Purification of Multiplicity Forms of the Enzyme

Abstract: Some of the biochemical properties of a crude lipase enzyme from Rhizopus arrhizus were determined. The enzyme displayed maximal catalytic activity at рН 9.0 and temperature of 35ºС. It was stable at basic values of pH and 40°C and in the presence of detergents. Lipase showed substrate specificity against different plant oils. Three multiplicity forms of the enzyme (Lip I, Lip II and Lip III) were isolated by gel chromatography. They differed in their molecular weight (Lip I-80 000 Da, Lip II-39 700 Da and Lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This gradual increase in FFA% with temperature can be explained by the well‐known fact that increasing the reaction temperature by 10°C results in doubling the rate of a chemical reaction (Wijaya, Wijaya, & Mehta, 2015). The lower values detected at 8°C could have been due to the reduction in the activity of lipase at lower temperatures since its optimal activity was at 35°C (Dobrev, Zhekova, Nedelcheva, Chochkov, & Krastanov, 2014). Eliseeva, Yurina, and Hovhannisyan (2017) reported that fatty acid composition significantly changed during accelerated storage of walnuts, with a decrease in polyunsaturated acids and an increase in the saturated fatty acid contents of the tested items during storage.…”
Section: Resultsmentioning
confidence: 99%
“…This gradual increase in FFA% with temperature can be explained by the well‐known fact that increasing the reaction temperature by 10°C results in doubling the rate of a chemical reaction (Wijaya, Wijaya, & Mehta, 2015). The lower values detected at 8°C could have been due to the reduction in the activity of lipase at lower temperatures since its optimal activity was at 35°C (Dobrev, Zhekova, Nedelcheva, Chochkov, & Krastanov, 2014). Eliseeva, Yurina, and Hovhannisyan (2017) reported that fatty acid composition significantly changed during accelerated storage of walnuts, with a decrease in polyunsaturated acids and an increase in the saturated fatty acid contents of the tested items during storage.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 A shows that 25 °C proved to be the optimal temperature for maximum lipolytic activity of the purified lipase. In general, the Mucoromycota extracellular lipases isolated so far had an optimum temperature over 25 °C [ 20 , 21 , 22 , 23 ]. The enzyme also proceeded well at 30 and 40 °C, exhibiting 92% and 56% relative activities, respectively.…”
Section: Resultsmentioning
confidence: 99%